THE ROLE OF HUMANS IN ORGANIZING DESIGN PROCESSES WITH BIM TECHNOLOGIES (World Bulletin of Social Sciences, 2024)
This article addresses the role of humans in the organization of design processes when using Building Information Modeling (BIM) technologies. By examining the history of BIM technology, its stages, and the impact of human involvement, the article highlights the importance of human expertise and collaboration throughout the entire lifecycle of a building project. The significance of human decision-making in each phase of BIM—from planning and design to operation—is explored, demonstrating how effective management and skilled professionals are essential for the successful implementation of BIM